Clinical value of Beery visual-motor integration and Beery VMI supplemental tests in Chinese preschoolers: a modified replication cross-sectional study - Tang, Xin; Xu, Xuan; Wang, Cong; Ao, Lijuan (Frontiers in Pediatrics, 2025)
ObjectivePrevious studies have indicated that visual-motor performance is affected by cultural variations. This study aimed to examine differences between the proportion of children with poor visual-motor integration (VMI) performance in published population norms with that in the sample population of this study and to assess the predictive value of the visual perception(VP) and motor coordination(MC) scores in explaining VMI variance in Chinese preschoolers.MethodsA random sample of 421 children ageds 3.0–6.11 years (mean age, 4.51 ± 0.93) participated in this study. The Beery VMI, VP, and MC were administered in sequence by qualified raters.ResultsThe standard scores of VMI in all age groups of this study were significantly better than those in U.S. norms. Overall, 61 (14.5% of the total sample) and 6 (1.4% of the total sample) children did poorly in the VMI test using study population norms and published population norms, respectively. The proportion of children with poor VMI performance using published norms was significantly lower compared with that using study sample population norms (p < 0.001). Multiple regression analysis showed that VP and MC were significantly related to the VMI (VP: β = 0.185, p < 0.001; MC: β = 0.400, p < 0.001) and 25.0% (F = 69.571, dF = 2, p < 0.001) variance of VMI could be explained by VP and MC.ConclusionOur findings support that the effects of culture should be considered when interpreting the results of Beery VMI using published norms, especially in poor performance diagnosis. Our findings further support that three tests should be assessed individually during the visual perception examination regardless of cultural context. Chinese preschooler–based norms need to be established in future investigations to determine the diagnostic value of the Beery VMI.